Analisis Pemanfaatan AI sebagai Media Pembelajaran Meningkatkan Motivasi Belajar PAI - nurandita; jasiah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
The development of Artificial Intelligence in education has encouraged a shift in Islamic Religious Education from conventional instruction toward more interactive, adaptive, and digitally relevant learning experiences. Previous studies have mostly discussed digital media in general, but they have not specifically examined how AI functions as a learning medium to improve motivation in Islamic Religious Education. The research problem is how the use of AI as a learning medium can increase students’ motivation in Islamic Religious Education, and the objective is to analyze its forms of use and contribution to student engagement. The data were processed through library research by selecting, reading, classifying, and interpreting Indonesian-language journals and books published between 2020 and 2025. The findings show that AI can be used to design teaching materials, quizzes, chatbots, virtual tutors, moral case studies, and instant feedback that improve attention, confidence, independence, and learning participation. This study concludes that AI is effective as a supporting medium for learning motivation in Islamic Religious Education, but teacher guidance remains necessary to ensure alignment with Islamic values, academic ethics, and moral formation.